Broken hollow carbon spheres decorated by gold nanodendrites as the advanced electrochemical sensing platform for sensitive tracing of morphine in human serum and saliva - Imanzadeh, Hamideh; Khataee, Alireza; Hazraty, Leila; Amiri, Mandana (Elsevier Science Sa, 2024)
In this study, an Au nanodendrites/broken hollow carbon spheres (Au NDs/BHCS) nanocomposite was prepared as an effective electrochemical sensor for detecting ultra-trace morphine (MPH) and exhibited advanced performance. The morphology, structure, and electrochemical behavior of the synthesized BHCS showed that the fractured spheres with a large specific surface area, high porosity, and good conductivity which can facilitate the transfer electrons at the sensor interface and afford an effective platform for electrochemical deposition of gold nanodendrites. Additionally, the catalytic property of Au nanodendrites is integrated with the electrochemical assay to reach high sensitivity for MPH detection. Benefiting from the synergistic effect of Au NDs and BHCS, the Au NDs/BHCS sensor demonstrated an outstanding electrochemical sensing performance toward MPH with a wider linear range of 0.01-300 mu M and an ultralow detection limit of 8.3 nM. The introduced electrochemical sensor offers a promising method for highly sensitive and selective morphine sensing. Furthermore, the fabricated nanosensor was employed to determine MPH in spiked serum and saliva samples and indicated satisfactory recovery in the 97-100% range. This work supplies a new road for the expansion of validated platforms for onsite screening of illegal drugs, which is essential in clinical settings and forensics.
Keywords: Morphine; Electrochemical sensor; Au nanodendrites; Broken hollow carbon spheres; Nanocomposite